2016
DOI: 10.15576/asp.fc/2016.15.3.91
|View full text |Cite
|
Sign up to set email alerts
|

The Peat-Forming Process of Degraded Raised Peat-Bog Baligówka

Abstract: Streszczenie. Ludzka działalność to obecnie obok zmian klimatycznych podstawowy czynnik zagrażający terenom bagiennym na całym świecie. Główne zagrożenia to zabiegi odwadniające oraz eksploatacja złóż torfowych. Na negatywną działalność człowieka w sposób szczególny narażone są ekosystemy wrażliwe, do jakich niewątpliwie należą torfowiska, szczególnie typu wysokiego. Głównymi komponentami tych ekosystemów są rośliny stenotopowe, co w znaczący sposób wpływa na ich podatność na szybką degradację. Nawet niewielki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, the use of remote sensing and GIS data allows for a much more precise determination of the range and shape of the object, as well as its division [25]. The range of melioration and exploitation of peat in the Baligówka peat bog visible in the ALS model and delimited in this study is slightly greater than estimated by the authors of previous publications [22,23].…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…However, the use of remote sensing and GIS data allows for a much more precise determination of the range and shape of the object, as well as its division [25]. The range of melioration and exploitation of peat in the Baligówka peat bog visible in the ALS model and delimited in this study is slightly greater than estimated by the authors of previous publications [22,23].…”
Section: Discussionmentioning
confidence: 58%
“…The overgrowing of the Baligówka peat bog by medium and high vegetation is a symptom of degradation of its ecosystem-in natural conditions, the area of the bog would be too wet, unstable, as well as poor in nutrients to grow tall shrubs or trees [15,23,28]. Many research indicated that peatland drainage may have a long-term effect on the structure of the phytocoenoses in marshland habitats [44] and biophilic elements exports [45].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations